Impact of COVID-19 morbimortality of oncological patients in Teresina-PI (Research, Society and Development, 2022)
The high mortality rate of covid-19 6.7% worldwide, (Turaga & Girotra, 2020), associated with a high transmissibility rate, requires a more targeted study for a portion of the population, which is within the comorbidities, which are cancer patients. Objectives: To verify changes in the hospitalization rates of cancer patients, and the influence of COVID-19 on the death of cancer patients. Methodology: Retrospective study that consists of analyzing the hospitalization and mortality rate of cancer patients between April 2019 and April 2021, through analysis of data available in open databases such as Opendatasus, datasus and the website of the health department of the state of Piauí. The present study has a cross-sectional statistical analysis, which obtained a P